Synthesis of Bacteriophage M13-Specific Proteins in a DNA-Dependent Cell-Free System II. In Vitro Synthesis of Biologically Active Gene 5 Protein - Konings, Ruud N. H. (1973)
It is shown that gene 5 protein of bacteriophage M13 is one of the major proteins synthesized in vitro under the direction of M13 replicative-form DNA. By means of DNA-cellulose chromatography, this protein has been purified to homogeneity and its biological characteristics have been compared with those of its native counterpart. Like native gene 5 protein, the purified, in vitro-synthesized protein binds tightly and selectively to single-stranded, but not to double-stranded, DNAs. These results suggest that truly functional gene 5 protein is made in the cell-free system.